Photodegradation of Phenol over a Hybrid Organo-Inorganic Material: Iron(II) Hydroxyphosphonoacetate - Bazaga-García, Montse; Cabeza-Díaz, Aurelio; Olivera-Pastor, Pascual; Santacruz-Cruz, María Isabel; Pérez-Colodrero, Rosario Mercedes; García-Aranda, Miguel Ángel (American Chemical Society, 2012)
Water treatment is a hot topic, and it will become much more important in the decades ahead. Advanced oxidation processes are being increasingly used for organic contaminant removal, for example using photo-Fenton reactions. Here we report the use of an organo-inorganic hybrid, Fe[HO3PCH(OH)COO]·2H2O, as Fenton photocatalyst for phenol oxidation with H2O2 under UVA radiation. Preactivation, catalyst content, and particle size parameters have been studied/optimized for increasing phenol mineralization. Upon reaction, iron species are leached from the catalyst making a homogeneous catalysis contribution to the overall phenol photo-oxidation. Under optimized conditions, the mineralization degree was slightly larger than 90% after 80 min of irradiation. Analysis by X-ray photoelectron spectroscopy revealed important chemical modifications occurring on the surface of the catalyst after activation and phenol photodegradation. The sustained slow delivery of iron species upon phenol photoreaction is advantageous as the mixed heterogeneous−homogeneous catalytic processes result in very high phenol mineralization.
Keywords: Química física; Iron(II) Hydroxyphosphonoacetate; Phenol; Metal phosphonates; Photodegradation